The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.1509/jmkr.47.1.75
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Analysis of Imitation Behavior across New Buyers at an Online Grocery Retailer

Abstract: For Internet retailers, demand propagation varies not only through time but also over space. The authors develop a Bayesian spatiotemporal model to study two imitation effects in the evolution of demand at an Internet retailer. Building on previous literature, the authors allow imitation behavior to be reflected both in geographic proximity and in demographic similarity. As these imitation effects can be time varying, the authors specify their dynamics using a “polynomial smoother” embedded within the Bayesian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
70
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(74 citation statements)
references
References 53 publications
(88 reference statements)
4
70
0
Order By: Relevance
“…The installed base is the total number or size of the technologies adopted in the peer group. Using the installed base to explain diffusion of a product or technology has been common in the literature [16,26,[30][31][32][33][34][35][36].…”
Section: Empirical Challenges To Estimate Peer Effectsmentioning
confidence: 99%
“…The installed base is the total number or size of the technologies adopted in the peer group. Using the installed base to explain diffusion of a product or technology has been common in the literature [16,26,[30][31][32][33][34][35][36].…”
Section: Empirical Challenges To Estimate Peer Effectsmentioning
confidence: 99%
“…Our analysis is informed by the literature on the role of proximity in innovation diffusion. It has been shown that spatial proximity has a positive influence on the diffusion of innovation (Agrawal et al, 2008;Bell & Song, 2007;Bronnenberg & Mela, 2004;Choi et al, 2010;Garber et al, 2004).…”
Section: Theoretical Overview and Hypothesesmentioning
confidence: 99%
“…Previous literature has suggested that supply-side factors, such as broader product variety (Brynjolfsson, Hu, and Smith 2003;Clemons, Gao, and Hitt 2006;Hinz, Eckert, and Skiera 2011), contribute to the emergence of the long tail. Others have focused on demand-side factors, such as reduced search costs (Brynjolfsson, Hu, and Smith 2006;Cachon, Terwiesch, and Xu 2008) and preference isolation (Choi, Hui, and Bell 2010).…”
Section: The Long Tail Of Demandmentioning
confidence: 99%